Analisis Perbandingan Metode AHP dan Metode MFEP Pada Sistem Pendukung Keputusan Pemilihan Vendor - Yuda Aji Pramukti; Septi Andryana (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Vendor is a party in the form of a company that provides goods and services to consumers or other business actors. Pasar Minggu Regional General Hospital is one of the Class B Non-Educational General Hospitals located in the heart of South Jakarta. The selection of vendors at Pasar Minggu Hospital was previously still using the traditional system and had not used it. The traditional method used previously often had several problems, starting from the administration of vendor data that was not accurate, as well as writing vendor data that was always wrong, then there was negligence in vendor assessment, and up to vendor selection that was not in accordance with the right mechanism. From these problems, Pasar Minggu Hospital requires a Decision Support System application in searching for vendors to be selected for a project. Because of this, Pasar Minggu Hospital plans to make a Decision Support System application to carry out the process of selecting the best vendor and in accordance with the criteria determined by the management of Pasar Minggu Hospital. The criteria between vendors include C1 (Finance), C2 (Performance), C3 (Safety) and C4 (Quality). On the Decision Support System website there are 5 menus, namely Company Data, Data Criteria, Criteria Comparison, Assessment Data and Analysis Results. In the calculation using the appropriate AHP consistency ratio of 0.10, it means that the data is declared consistent. And in the MFEP method the total Factor Weight is 9.00 with details of Finance 2.00, work safety 2.00, quality 3.00 and performance 2.00. From the calculation results of the two methods above that the first order of comparison of vendor results is occupied by PT. Bangun Rezeki with a percentage using AHP of 87%, and using MFEP of 71%, in second position by PT. Building Award with a percentage of 81% and 73% with MFEP. And the last position by PT. Ocean figures with a percentage of 72% using AHP and 56% using MFEP.